Extracorporeal photopheresis as an immunomodulatory treatment modality for chronic GvHD and the importance of emerging biomarkers - Bojanic, Ines; Worel, Nina; Pacini, Carolina P.; Stary, Georg; Piekarska, Agnieszka; Flinn, Aisling M.; Schell, Kimberly J.; Gennery, Andrew R.; Knobler, Robert; Lacerda, João F.; Greinix, Hildegard T.; Pulanic, Drazen; et al. (Frontiers in Immunology, 2023)
Haematopoietic stem cell transplantation (HSCT) is the treatment of choice for malignant haematological diseases. Despite continuous improvements in pre- and post-transplantation procedures, the applicability of allo-HSCT is limited by life-threatening complications such as graft-versus-host disease (GvHD), engraftment failure, and opportunistic infections. Extracorporeal photopheresis (ECP) is used to treat steroid resistant GvHD with significant success. However, the molecular mechanisms driving its immunomodulatory action, whilst preserving immune function, require further understanding. As ECP is safe to administer with few significant adverse effects, it has the potential for earlier use in the post-HSCT treatment of GvHD. Thus, further understanding the immunomodulatory mechanisms of ECP action may justify more timely use in clinical practice, as well as identify biomarkers for using ECP as first line or pre-emptive GvHD therapy. This review aims to discuss technical aspects and response to ECP, review ECP as an immunomodulatory treatment modality for chronic GvHD including the effect on regulatory T cells and circulating vs. tissue-resident immune cells and consider the importance of emerging biomarkers for ECP response.